Knowledge And Practice on Prevention and Control of Dengue Among Homemaker in Bharatpur Metropolitan, Chitwan - Adhikari, Sudip; Choudhary, Pradeep; Upadhyay, Hari Prasad; Adhikari, Alina; Kalakheti, Kamal; Sedain, Prativa (International Journal of Silkroad Institute of Research and Training, 2023)
Background: Dengue is a viral infection transmitted to humans through the bite of infected mosquitoes. The dengue virus (DENV) is one of the mosquito-borne viral diseases in the world today. Two main arthropod vectors are responsi-ble for transmission of dengue viruses: Aedes aegypti and Aedes albopictus. The Aedes aegypti mosquito is the main vector for the spread of dengue fever. Methods: An analytical cross-sectional study was conducted among home makers of Bharatpur. Data was analyzed using descriptive and inferential statistical tools in SPSS-20. p-value <0.05 was considered as statistically significant. Results: In this study 60.0% have Fair level of knowledge 39.8% have poor level of knowledge. There was no good practice. The majority of respondents 78.6% show Good level of practice and minority 22.4% showed poor level of practice. Conclusions: We can conclude that majority of the respondents had fair knowledge regarding dengue. Despite of the fair knowledge level, the majority of the respondent had good practices such as use of mosquito net, covering house-hold containers, covering water tank, invert the water holding containers.